2020
DOI: 10.1002/edn3.67
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a coastal North Sea fish community: Comparison of aquatic environmental DNA concentrations to fish catches

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…Hänfling et al (2016) discerned that metabarcoding assay read abundances were positively correlated with findings of long-term concomitant capture-based surveys of fishes in three United Kingdom lakes. Van Bleijswijk et al (2020) found that fish biomass caught in fyke net surveys in a tidal inlet between the North and Wadden Seas showed weak positive correlation with metabarcoding sequence read abundances for just the eight most abundant species. Positive correlations with sequence reads at higher taxonomic levels have appeared more common in most studies (Thomsen et al 2016;Gillet et al 2018), although since different taxa in families often are not ecological equivalents (e.g., benthic invertivore darters and several piscivorous species in Percidae), those results are less useful than comparisons at the species level.…”
Section: Experiments Series A: Relative Abundances Of Species From Metabarcoding Assaysmentioning
confidence: 95%
“…Hänfling et al (2016) discerned that metabarcoding assay read abundances were positively correlated with findings of long-term concomitant capture-based surveys of fishes in three United Kingdom lakes. Van Bleijswijk et al (2020) found that fish biomass caught in fyke net surveys in a tidal inlet between the North and Wadden Seas showed weak positive correlation with metabarcoding sequence read abundances for just the eight most abundant species. Positive correlations with sequence reads at higher taxonomic levels have appeared more common in most studies (Thomsen et al 2016;Gillet et al 2018), although since different taxa in families often are not ecological equivalents (e.g., benthic invertivore darters and several piscivorous species in Percidae), those results are less useful than comparisons at the species level.…”
Section: Experiments Series A: Relative Abundances Of Species From Metabarcoding Assaysmentioning
confidence: 95%
“…In this study, we propose a more direct method for inferring the absolute abundance of fish species from multiple sampling locations by combining eDNA metabarcoding with qPCR analysis, which assesses the total abundance of eDNA amplified by the universal marker used for metabarcoding. Fish-specific eDNA concentrations are then calculated from the ratios of fish species-specific read counts over the total read count of a sample (metabarcoding) multiplied by the total eDNA concentration estimated with qPCR (van Bleijswijk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is because beta diversity is more complicated to record and synthesize from multiple sources, as it is often reported using different metrics, also calling for more standardized reporting of data enabling future assessments and meta-analyses. Nonetheless, beta diversity remains an important component of diversity and can give different results if analysed through DNA or traditional methods (Bleijswijk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%